2016
DOI: 10.4269/ajtmh.15-0335
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, Behaviors, and Perceptions of Community-Led Total Sanitation and Their Relation to Improved Sanitation in Rural Zambia

Abstract: Abstract. Inadequate hygiene and sanitation remain leading global contributors to morbidity and mortality in children and adults. One strategy for improving sanitation access is community-led total sanitation (CLTS), in which participants are guided into self-realization of the importance of sanitation through activities called "triggering." This qualitative study explored community members' and stakeholders' sanitation, knowledge, perceptions, and behaviors during early CLTS implementation in Zambia. We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 9 publications
1
50
0
Order By: Relevance
“…Being unaware of disease spread was reported to be a barrier for implementation in two studies on a community-and an approach containing elements of psychosocial theories Lawrence et al, 2016). Conversely, being aware of disease spread was considered a facilitator for implementation in an approach based on sanitation and hygiene messaging, a community-based approach and an approach containing elements of psychosocial theories Andrade, 2013;Brooks et al, 2015;Lawrence et al, 2016;Smith et al, 2004;. Another factor that was a facilitator for the implementation of community-based approaches was the induction of feelings of shame and disgust in response to old habits and practices (Lawrence et al, 2016;Malebo et al, 2012).…”
Section: • Planning Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being unaware of disease spread was reported to be a barrier for implementation in two studies on a community-and an approach containing elements of psychosocial theories Lawrence et al, 2016). Conversely, being aware of disease spread was considered a facilitator for implementation in an approach based on sanitation and hygiene messaging, a community-based approach and an approach containing elements of psychosocial theories Andrade, 2013;Brooks et al, 2015;Lawrence et al, 2016;Smith et al, 2004;. Another factor that was a facilitator for the implementation of community-based approaches was the induction of feelings of shame and disgust in response to old habits and practices (Lawrence et al, 2016;Malebo et al, 2012).…”
Section: • Planning Skillsmentioning
confidence: 99%
“…A facilitator for the implementation of a social marketing-based approach was living in city centres, as people living there tend to be wealthier (Emerging Markets Consulting, 2014). Living in remote areas, with lesser access to water or sanitation facilities, was suggested to be a barrier towards the implementation of a community-based approach (Lawrence et al, 2016) or a programme using sanitation and hygiene messaging (Graves et al, 2013).…”
Section: • Physical Contextmentioning
confidence: 99%
“…Lawrence et al [48] identified shame from the CLTS triggering as one of the most important factors for behavioural change in rural Zambia. Yet, CLTS may also influence adherence through other social and emotive factors that include disgust, pressure from hierarchical powers and community groups, and competition among villages to achieve ODF status.…”
Section: Impact On Behaviour and Attitudesmentioning
confidence: 99%
“…From studies on this basis using experimental public goods games (PGG), economic models of peer pressure, microfinance institutions and natural resource usage; peer pressure mechanism is found to increase cooperative behaviour [20][21][22][23][24]. The strategy has been used in the case of sanitation in Zambia, India, Bangladesh [25][26]. These programs are known to use shaming, as a strategy in these schemes.…”
Section: Role Of Networkmentioning
confidence: 99%